When comes the spring - Oke, Janette, 1935- (Oke, Janette, 1935- Canadian West series, 2005)
Elizabeth, a lovely young eastern school teacher, has spent a year teaching in a one-room schoolhouse. After her marriage to a Royal Canadian Mountie she must face many hardships at his outpost in the far north.